STRENGTHENING EFFORTS TO RELIGIOUS MODERATION WITH COMMUNICATION STRATEGIES IN THE PTKIN ENVIRONMENT OF NORTH SUMATERA - Mhd Latip Kahpi; Asriana (Waniambey: Journal of Islamic Education, 2025)
This study aims to analyze efforts to strengthen religious moderation in the State Islamic Religious College (PTKIN) environment in North Sumatra through the communication strategies applied. Religious moderation is a very relevant concept in maintaining harmony and harmony between religious communities, especially in the context of campuses that have diverse student backgrounds. This study uses a qualitative approach with descriptive analysis to identify the communication strategies applied, the obstacles faced, and the efforts made to overcome these obstacles. The results of the study indicate that PTKIN in North Sumatra have implemented various communication strategies such as curriculum integration based on religious moderation, inclusive learning methods, and the use of social media as a means of continuous education. However, there are still several obstacles, including a lack of in-depth understanding of religious moderation, social and cultural resistance, and limited resources. To overcome these obstacles, continuous training, development of a more relevant curriculum, and optimization of the use of digital technology are needed. This study contributes to the development of more effective communication strategies in strengthening religious moderation in higher education environments, especially in PTKIN North Sumatra.